Reduced Expression of BjRCE1 Gene Modulated by Nuclear-Cytoplasmic Incompatibility Alters Auxin Response in Cytoplasmic Male-Sterile Brassica juncea - Yang, Xiaodong; Liu, Xunyan; Lv, Wenhui; Li, Lu; Shi, Qianqian; Yang, Jinghua; Zhang, Mingfang (PLOS ONE, 2012)
The signal from organelle to nucleus, namely retrograde regulation of nuclear gene expression, was largely unknown. Due to the nuclear-cytoplasmic incompatibility in cytoplasmic male-sterile (CMS) plants, we employed CMS Brassica juncea to investigate the retrograde regulation of nuclear gene expression in this study. We studied how reduced BjRCE1 gene expression caused by the nuclear-cytoplasmic incompatibility altered the auxin response in CMS of B. juncea. We isolated the BjRCE1 gene that was located in the nucleus from B. juncea. Over-expression of BjRCE1 enhanced auxin response in transgenic Arabidopsis. The expression of BjRCE1 was significantly reduced in CMS compared with its maintainer fertile (MF) line of B. juncea. There were fewer lateral roots in CMS than MF under normal and treatment of indole-3-acetic acid (IAA) conditions. Expression patterns of several auxin-related genes together with their phenotypes indicated a reduced auxin response in CMS compared to MF. The phenotypes of auxin response and auxin-related gene expression pattern could be mimicked by inhibiting mitochondrial function in MF. Taken together, we proposed reduced expression of BjRCE1 gene modulated by nuclear-cytoplasmic incompatibility alters auxin response in CMS B. juncea. This may be an important mechanism of retrograde regulation of nuclear gene expression in plants.